Prevention and control of fungal contamination and Mycotoxicosis - Kaur, Gurpreet; Chandra, Mudit (Indian Farming, 2015)
Feed and fodder contamination can occur in field conditions as well as during processing and storage of harvested products whenever, environmental conditions are favourable for the growth of fungi. For gross identification of fungus and suspected mycotoxins in the feedstock, farmer can rely on certain changes that can indicate the presence of fungus in the feed and fodder. The methods adopted to prevent contamination are not commercially popular and therefore decontamination of feed is limited but prevention is the best strategy.